The Implementation of Glickman’s Ten-Step Collaborative Supervision in Enhancing Teacher Professionalism at SMAN 2 Sawang - Ramhiyati, Ramhiyati; Sahdan, Sahdan; Fazari, Tajul (UIR Press, 2026)
This study aims to analyze the implementation of collaborative supervision based on Glickman's ten-step model in enhancing teacher professionalism at SMAN 2 Sawang. The model includes the stages of clarifying, listening, reflecting, presenting, re-clarifying, problem-solving, encouraging, negotiating, standardizing, and final reflecting, systematically applied through a participatory approach between the principal and teachers. This research employs a qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that active teacher involvement in all stages of supervision contributes to improved professionalism indicators, including enhanced pedagogical competence, clearer development directions, and increased commitment to transforming teaching practices. Supervision conducted in a collaborative atmosphere successfully fosters equal professional relationships and strengthens a reflective culture within the school environment. These findings reinforce the literature on the effectiveness of collaborative supervision approaches in creating a sustainable learning ecosystem and supporting the transformation of quality culture in secondary education.